Nonstructural Damages of Reinforced Concrete Buildings Due to 2015 Ranau Earthquake - M. I., Adiyanto; Majid, Taksiah A.; Fadzli, Mohamed Nazri (AIP Publishing, 2017)
On 15th June 2016 a moderate earthquake with magnitude Mw5.9 was occurred in Sabah, Malaysia. Specifically, the epicentre was located at 16 km northwest of Ranau. Less than two days after the first event, a reconnaissance mission took action to investigate the damages on buildings. Since the reinforced concrete buildings in Ranau were designed based on gravity and wind load only, a lot of minor to severe damages was occurred. This paper presents the damages on the nonstructural elements of reinforced concrete buildings due to Ranau earthquake. The assessment was conducted via in-situ field investigation covering the visual observation, taking photo, and interview with local resident. Based on in-situ field investigation, there was a lot of damages occurred on the nonstructural elements like the brick walls. Such damages cannot be neglected since it can cause injury and fatality to the victims. Therefore, it can be concluded that the installation of nonstructural elements should be reviewed for the sake of safety.